1993
DOI: 10.1128/jb.175.20.6704-6710.1993
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin-binding protein 2 inactivation in Escherichia coli results in cell division inhibition, which is relieved by FtsZ overexpression

Abstract: Aminoacyl-tRNA synthetase mutants of Escherichia coli are resistant to amdinocillin (mecillinam), a P-lactam antibiotic which specifically binds penicillin-binding protein 2 (PBP2) and prevents cell wall elongation with concomitant cell death. The leuS(Ts) strain, in which leucyl-tRNA synthetase is temperature sensitive, was resistant to amdinocillin at 37°C because of an increased guanosine 5'-diphosphate 3'-diphosphate (ppGpp) pool resulting from partial induction of the stringent response, but it was sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
100
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 57 publications
6
100
0
Order By: Relevance
“…However, sixfold overproduction of FtsZ (6 × 10 ¹5 M IPTG) permitted essentially all cells to grow in the presence of mecillinam (Table 1). This corroborates our previous observation that pZAQ confers mecillinam resistance but pAQ does not (Vinella et al, 1993).…”
Section: Mecillinam Resistance Via Overexpression Of Ftsq Ftsa and Ftszsupporting
confidence: 92%
See 4 more Smart Citations
“…However, sixfold overproduction of FtsZ (6 × 10 ¹5 M IPTG) permitted essentially all cells to grow in the presence of mecillinam (Table 1). This corroborates our previous observation that pZAQ confers mecillinam resistance but pAQ does not (Vinella et al, 1993).…”
Section: Mecillinam Resistance Via Overexpression Of Ftsq Ftsa and Ftszsupporting
confidence: 92%
“…We originally observed that the multicopy plasmid pZAQ, which causes overproduction of FtsQ, FtsA and FtsZ from their natural promoters, conferred mecillinam resistance on its host, whereas pAQ, lacking a functional ftsZ gene, did not (Vinella et al, 1993). We wished to see whether amplification of FtsZ alone was sufficient to confer mecillinam resistance.…”
Section: Mecillinam Resistance Via Overexpression Of Ftsq Ftsa and Ftszmentioning
confidence: 99%
See 3 more Smart Citations